On the Future of Bitcoin and Altcoins as Currencies, Tokens for Smart Contracts, and Instruments of Commitment (IOCs): Some Considerations Regarding Blockchain Applications - Eibner, Wolfgang; Rätsch, Kurt; Schulz, Antonio; Rolapp, Andre (Estonian Discussions on Economic Policy, 2018)
In the article we discuss following hypotheses:Thesis 1: „Private Cryptocurrencies will not be seen as an alternative to Fiat-Money in the near future or any time soon.“Thesis 2: „Initial Coin Offerigs (ICOs) can increasingly become an alternative to traditional Venture Capital Financing and Token might enable to build smart contracts on a decentralized infrastructure.“In the article we explain Blockchain technology and its possible applications in a very wide range. Also are shown main cryptocurrencies in their functions as possible future currencies, as platform token, and utility token necessary for Smart Contracts, or equity token, especially for Initial Coin Offerings. A main part of the article is the discussion of possible risks in the these applications of cryptocurrencies or token, referring explicitly to technical risks, economical risks like the stability of the financial markets (volatility, deflation), but also the severe problem of manipulated markets, supplemented by some considerations on legal issues.